Examining the efficacy of Electronic Document Management System and Employees ’ Perceptions of its Usefulness at Sokoine University of Agriculture - Malekani, Andrew Watson (University of Dar es Salaam Library Journal, 2023)
This study was conducted at the Sokoine University of Agriculture (SUA) to assess the efficacy of Electronic Document Management System (EDMS) in the accessibility and use of records at the Sokoine University of Agriculture. Specifically, the study sought to assess employees ' perceptions of the use of the Electronic Document Management System at the Sokoine University of Agriculture and identify the challenges facing employees in accessing and using EDMS at the Sokoine University of Agriculture. The study used a cross-section research design whereby the data were collected at one time based on two approaches which are qualitative and quantitative. The study involved 100 SUA staff. These were selected from a population of 1308 SUA staff by using purposive, sampling simple random, and systematic random sampling techniques. Results indicate that the majority of the respondents agreed that the use of SUA €“EDMS fostered efficiency in management decisions, and perceive that the use of SUA €“EDMS increases accountability. Among all the independent variables, duration at work and rating on effectiveness were found to have a unique contribution to a variation in the perceived usefulness of EDMS. It was concluded that the use of EDMS is very essential for the well-functioning of the organization in terms of faster access to records and which spearheads effective and efficient delivery of services to customers in the organization. The study recommends improving internet speed as one measure to improve the EDMS.